Isolation and Identification of Lactic Acid Bacteria from Red Dragon Fruit (Hylocereus polyrhicus) as Exopolysaccharide Producers - Tatebale, Rivaldo; Naharia, Orbanus; Lawalata, Helen J (Indonesian Biodiversity Journal, 2024)
Cherry tomatoes are a type of Red Dragon Fruit that has various benefits, including lowering cholesterol levels, preventing colon cancer, and strengthening the working power of muscles. Isolation of LAB isolated from Dragon Fruit as a production material for EPS. This study aims to isolate and identify LAB as a producer of EPS from red dragon fruit (Hylocereus polyrhiruz), which can produce exopolysaccharides. This research uses a descriptive research method. Data from experimental research in the laboratory obtained 10 LAB isolates, namely isolates NG1, NG2, NG3, NG4, NG5, NG6, NG7, NG8, NG9 and NG10. Based on the identification results, isolate NG1 has similarities with the genus Lactococcus (spherical, gram-positive, nonmotile, non-spore). While isolates NG2, NG3, NG4, NG5, NG6, NG7, NG8, NG9 and NG10 have similarities with the genus Lactobacillus (rod form, nonmotile, gram-positive). Based on the morphological characteristics, which are gram-positive, catalase-negative and non-spore. The ten isolates of lactic acid bacteria are capable of producing EPS. these are the results of EPS acquisition, namely: NG1(152.1 mg/L), NG2(127.9 mg/L), NG3(134.6 mg/L), NG4(130.9 mg/L), NG5(137 mg/L), NG6(139.2 mg/L), NG7(204.9 mg/L), NG8(156.2 mg/L), NG9(136.4 mg/L), and NG10 (157, 3 mg/L). The highest amount of EPS was isolated NG7 at 204.9 mg/L. Meanwhile, the lowest EPS was isolated NG4 at 130.9 mg/L.